The microstructure and mechanical properties of Ni/Al2O3 composites by in-situ generated CaAl12O19 and ZrO2 via hot pressing sintering. Issue 9 (15th June 2020) - Zhang, Xi; Zeng, Yanan; Liang, Jinsheng; Li, Junguo; Hao, Suju; Wang, Yajun
Abstract: Ni/Al2 O3 composites with a varying mass fraction of CaZrO3 (0–12 wt%) were prepared by vacuum hot pressing sintering at 1650 °C under a pressure of 30 MPa for 30 min to investigate how CaZrO3 affect the mechanical properties and morphology of the composites. The results show that CaZrO3 can react with Al2 O3 and form new strengthening and reinforcing phases of CaAl12 O19 and ZrO2, which can promote complete densification and solve the problem of uneven distribution due to the poor wettability between Al2 O3 and Ni. Additionally, composites showed satisfactory mechanical properties when 6.0–9.0 wt% CaZrO3 was added and the major toughening mechanism involved the typical fracture of delamination and the transgranular mode.